(3JUejejGJ YQHjIs (3cJGH Jdhjf (B= Arabic patterns : coloring books - (3HhQLhG, Ljgs ((3GdQjGVs (3ecJHI LQjQs, 2016)
(3gPg GdeLehYI GdQGFYI hGdeThbI GdechfI ef (B31 (3JUejekG ef JUejeGJ GdgfOSjI eSJhMGI ef GdJUejeGJ GdgfOSjI eSJhMGI ef JUejeGJ Gdaf GdESdGej GdLejd GdeNJGQI ef CdHhe fGOQ jYhO ddbQf GdJGSY YTQ(B. (3hJTJed GdQSheGJ GdeJOGNdI Ydi CTcGd GdeVdYGJ hGdfLhe hGdRghQ hZjQgG ef GdQSheGJ PGJ GdJaGUjd QajYI ddeSJhis
(3fTQ gPG GdcJGH ef bHd JMJ YfhGf (BArabic allover patternss
(3jMJhj gPG GdcJGH Ydi hQb bGHd ddfRY djSgd Ydjc YQV CYeGdc GdafjIs
1 13
Keywords: (3GdJUeje GdRNQajs; (3GdJdhjfs